Determinants of implementation of child-parent psychotherapy to treat early childhood trauma: a reflexive analysis - Silje Marie Haga; Heidi Jacobsen; Thomas Engell (BMC Health Services Research)
Abstract Background Trauma experiences in early childhood can significantly impact children’s development. Child-Parent Psychotherapy (CPP) is an evidence-based treatment that addresses traumatic stress and child-parent attachment in children ages 0–6 years. Successful implementation of evidence-based interventions is challenging and presupposes a thorough understanding of the context in which it is being implemented. The objectives of this study were to explore the beliefs and experiences of therapists involved in the training and implementation of CPP in child and adolescent mental health- and child welfare services in Norway. The aim was to understand how health professionals experience implementation of CPP and identify determinants that could enhance or support the implementation process. Methods Therapists were recruited from two subsequent CPP-training courses at the Regional Centre for Child and Adolescent Mental Health. We conducted ten semi-structured focus group interviews with forty therapists. They were interviewed after approximately six months of an 18-month CPP training initiative and again at the end of the training. We used reflexive thematic analysis to identify themes and determinants from descriptions of beliefs, attitudes and experiences with the training and implementation of CPP. Results Four major themes were identified: (1) Intrinsic motivation due to alignment between personal needs and client needs, (2) Psychological readiness influences how therapists engage with CPP, (3) CPP offers welcomed flexibility and professional autonomy, but ambivalence emerges in practice, and (4) Leadership support is not the same as implementation leadership. These themes and determinants were often interconnected and multileveled, reflecting the complexity of implementation processes. Conclusions Implementation of CCP was influenced by determinants such as therapists’ intrinsic motivation, psychological readiness, and a balance between flexibility and intervention structure. Proactive leadership or strong self-leadership appears to be necessary to create opportunities for implementation engagement. The successful implementation of CPP appears to require tailoring to individual, organizational, and cultural needs.